2011
DOI: 10.1039/c1ee01213d
|View full text |Cite
|
Sign up to set email alerts
|

High mobility organic thin film transistor and efficient photovoltaic devices using versatile donor–acceptor polymer semiconductor by molecular design

Abstract: In this work, we report a novel donor-acceptor based solution processable low band gap polymer semiconductor, PDPP-TNT, synthesized via Suzuki coupling using condensed diketopyrrolopyrrole (DPP) as an acceptor moiety with a fused naphthalene donor building block in the polymer backbone. This polymer exhibits p-channel charge transport characteristics when used as the active semiconductor in organic thin-film transistor (OTFT) devices. The hole mobilities of 0.65 cm 2 V À1 s À1 and 0.98 cm 2 V À1 s À1 are achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
151
2
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 170 publications
(157 citation statements)
references
References 31 publications
3
151
2
1
Order By: Relevance
“…Of particular interest is the sensitivity of the polaron generation and decay with respect to the applied voltage. For all polymers, the voltage at which ground state bleaching and weak polaron absorption was first observed was 0.6 V. The HOMO values for PDPP-FPF, PDPP-FNF, PDPP-FAF, and PDPP-TNT were reported [30,31] to be very close to one another at 5.40, 5.34, 5.33, and 5.30 eV, respectively. At larger applied voltages, while additional bleaching of ground-state absorption was observed, the polaron signal started to decay, as illustrated by the drop in their corresponding absorption.…”
Section: Spectroeclectrochemistrymentioning
confidence: 84%
See 1 more Smart Citation
“…Of particular interest is the sensitivity of the polaron generation and decay with respect to the applied voltage. For all polymers, the voltage at which ground state bleaching and weak polaron absorption was first observed was 0.6 V. The HOMO values for PDPP-FPF, PDPP-FNF, PDPP-FAF, and PDPP-TNT were reported [30,31] to be very close to one another at 5.40, 5.34, 5.33, and 5.30 eV, respectively. At larger applied voltages, while additional bleaching of ground-state absorption was observed, the polaron signal started to decay, as illustrated by the drop in their corresponding absorption.…”
Section: Spectroeclectrochemistrymentioning
confidence: 84%
“…In this paper we investigate the optical properties of a series of furan substituted diketopyrrolopyrrole co-polymers with phenylene, naphthalene and anthracene co-monomer blocks: poly(3,6-difuran-2-yl-2,5-di(2-octyldodecyl)-pyrrolo [3,4-c]pyrrole-1,4-dione-alt-phenylene) (PDPP-FPF), poly(3,6-difuran-2-yl-2,5-di(2-octyldodecyl)-pyrrolo [3,4-c]pyrrole-1,4-dione-alt-naphthalene) (PDPP-FNF) and poly(3,6-difuran-2-yl-2,5-di(2-octyl dodecyl)-pyrrolo [3,4-c]pyrrole-1,4-dione-alt-anthracene) (PDPP-FAF) [30]. We also investigate a thipohene analogue to PDPP-FNF, Poly(3,6-dithiophene-2-yl-2,5-di(2-octyldodecyl)-pyrrolo [3,4-c] pyrrole-1,4-dione-alt-naphthalene) (PDPP-TNT) [31,32]. The molecular structure for all polymers is shown in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%
“…The HOMO level and E g ec of PDPP-TNT were reported to be −5.29 and 1.99 eV, respectively. 6 These results indicate that our PDPP-TDNT has a larger E g ec but a deeper HOMO level compared to the reported PDPP-TNT. It has been reported that electron-releasing substituents such as alkoxy groups on electron-donor units can tuned the HOMO level of the resulting conjugated polymers.…”
Section: Resultsmentioning
confidence: 45%
“…On the other hand, the absorption pattern of PDPP-TNT was reported to be reversed from PDPP-TDNT, which absorbed much more intensely at 500-800 nm than at 300-500 nm. 6 The absorption in the longer wavelength region can be attributed to intermolecular charge transfer between the electron-rich and electron-poor units in the polymer chain. This comparison suggests that the low absorption intensity of PDPP-TDNT in the longer wavelength region may result from less efficient charge transfer between the DNT and DPP moieties through the thiophene spacer due to the bulky alkoxy substituents on the naphthalene ring.…”
Section: Resultsmentioning
confidence: 99%
“…20 The introduction of 23 Although the crystallinity of the T-DPP-T based polymer was improved due to the rigidity of the arylenevinylene linkage, this did not change the hole mobility (measured at 0.2 cm 2 /Vs). In order to increase the overall planarity of the conjugated backbone, two fused aromatic systems, naphthalene (P15) 24 and…”
Section: Discussionmentioning
confidence: 99%